Implementation of a Fault-Tolerant AC/DC Converter for Permanent Magnet Synchronous Motor Drive Systems - Liu, Tian-Hua; Wang, Yu-Wei (Frontiers in Electronics, 2021)
Fault tolerant drive systems have played an increasing role for electric vehicles in order to improve reliability, availability, and to reduce maintenance. For safety reason, a fault-tolerant drive system, which includes some redundant devices and a traditional motor drive system, has been developed. This fault-tolerant system executes real-time fault detection, diagnosis, isolation, and control to make the fault-tolerant drive system operate normally even though some faults have happened. In this paper, an AC/DC converter faults, which includes a single-phase full-bridge rectifier diode fault, a three-phase full-bridge rectifier diode fault, and a DC-link capacitor fault are investigated. The fault-tolerant processes include fault detection, diagnosis, isolation, and control to improve the reliability of the drive system and reduce the disturbances during faulty interval. A digital signal processor, manufactured by Texas Instruments, type TMS320F2808, is used as a control center to achieve the fault tolerant processes. Experimental results validate theoretical analysis to demonstrate the correctness and feasibility of the proposed methods. The proposed method can be easily implemented in industrial products due to its simplicity.